Oblique Porous Composite as Evaporating "Cap": Do Desert Dunes Preserve Moisture by Capillary Barriers and Tilt of Their Slopes?. Issue 3 (11th March 2019) - Al‐Shukaili, A.; Al‐Busaidi, H.; Al‐Maktoumi, A.; Abdalla, O.; Shelukhina, O.; Kacimov, A. R.
Abstract: Evaporation from desert sand dunes is studied practically using laboratory columns and mathematically using both analytical and numerical modeling. On outcropping cliffs of the dunes of Buwshar (Oman), microstratification, with layers' thickness of 1–2 mm, was observed. Loose sand and consolidated core samples were collected for laboratory experiments. Imbibition into initially dry sand columns and ensuing steady state evaporation from a capillary fringe above a horizontal water table were studied. The evaporating, negative‐pressure topsoil of the columns was slanted mimicking the cliffs' tilt. In the columns plugged by a thin composite "cap" made by tooling the dune stratified clod, evaporation was impeded and reduced as compared with a homogeneous column. The same outlet evaporating boundaries were considered in HYDRUS‐2D simulations, which showed that 2‐D evaporation from a homogenous column was significantly higher than that from the column with a stratified "plug" at the top. Analytical solution for a 2‐D tension‐saturated homogeneous trapezium was obtained by conformal mappings of pentagon in the physical plane onto a rectangle in the Zhukovsky plain, via a reference plane. This solution combines the versatility of the Toth model, where topology of flow is controlled by an isobaric boundary of a flow tube, and of the Vedernikov model, which assumes a constant hydraulic conductivity in the negative pressure zone of a capillary fringe. Analytical formulae also manifest a decrease of the flow rate with the increase of the angle of tilt of an evaporating isobar. Plain Language Summary: Some sand dunes in arid deserts have moist volumes at relatively shallow depths under their dry and hot slopes. This perplexing water accumulation has been attributed to several factors, for example, dew and vapor condensing from the wind air of high humidity or stratification of aeolian deposits and ensuing capillary barriers to vertical infiltration after rare rainfall events. In this note we explore a potential impedance to a trivial 1‐D evaporation from a fully saturated horizon to a negative pressure isobar, stemming from its wavy (zig‐zag) shape and a thin oblique microstratified "cap" composed of millimeter‐thick layers. Our laboratory experiments with two sand columns (one homogeneous, with a tilted soil surface and another covered by a tilted cap) showed that the total steady state evaporation from a heterogeneous column is less, provided the volumes of the two are the same. This is confirmed in HYDRUS‐2D numerical simulations for trapezoidal domains. Analytical solutions illustrate the decrease of evaporation losses if the area of a homogeneous trapezium is fixed along the minimum distance between the inlet (water table) and outlet (soil surface), provided the soil is tension saturated. Key Points: Evaporation through a homogeneous soil column with a slanted top and a column with a microstratified "plug" at its top are compared Simulation in HYDRUS and analytical solutions for tension‐saturated 2‐D flows in trapezoidal domains illustrate reduction of evaporation Textural interbeddings of the sand dunes and obliqueness of their cliffs are hypothesized as counterevaporation moisture retention factors